Word Campion Superbike (Wsbk Mandalika) Kuta Lombok Nusa Tenggara Barat - Evitamala, Lilik; Anam, Khaerul; Hidayatulloh, Muhammad Riyan (Jurnal Porkes, 2022)
The purpose of this study was to determine the impact of WSBK on the level of tourist visits to fitness locations and increase in income as a personal traner since the Implementation of WSBK in 2021. This research method uses quantitative methods with population survey techniques in this study in three locations in Kuta Mandalika. finding method based on registration at customer service data analysis using percentage analysis. Based on the findings of the percentage results at the local fitness center, Novotel Lombok, and Badar Gym, the results show that the level of visits to the fitness workout location is categorized as "medium" (56%), at the Novotel Fitness location is in the "very good" category (80%), the third location Fitness Badar Gym is in the "Good" category (59%), The average personal trainer income at the Fitness location is 2.5 Million Novotel and Badar Gym does not use a Personal Trainer. The conclusion in this study is that WSBK has an impact on increasing visits to the Novotel fitness location during the event and has no effect on personal trainer income.